2008
DOI: 10.1245/s10434-008-9836-y
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Survival and Occasional Regression of Distant Melanoma Metastases after Adrenal Metastasectomy

Abstract: Adrenalectomy for melanoma metastatic to the adrenal gland provides good palliation of symptoms and is associated with prolonged survival in a selected cohort of patients. We report for the first time sustained complete regression of distant metastatic melanoma after bilateral adrenalectomy, suggesting a possible role for adrenal hormones in modifying melanoma progression in certain patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(45 citation statements)
references
References 35 publications
2
41
0
2
Order By: Relevance
“…In some series of patients where pain was the major complaint, adrenalectomy proved successful in relieving the pain, although survival was very poor [5,[72][73][74].…”
Section: Indicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In some series of patients where pain was the major complaint, adrenalectomy proved successful in relieving the pain, although survival was very poor [5,[72][73][74].…”
Section: Indicationsmentioning
confidence: 99%
“…Twenty years ago, there was some evidence that surgical resection of asymptomatic, small, and solitary adrenal metastasis could be potentially curative in patients with melanoma [24]. Two important and recent series assessing resection of isolated adrenal metastasis from melanoma have shown that adrenalectomy can provide excellent palliation of symptoms and, in a selected subset of patients, prolonged survival [73,91]. There were two patients with unexpected tumour resolution after adrenalectomy, perhaps related to the presence of high-affinity glucocorticoid receptors in the melanoma cells [73].…”
Section: Melanomamentioning
confidence: 99%
“…Slightly elevated risk of malignant melanoma was found among users of oral glucocorticoids [28]. Moreover, a clinical study demonstrating regression of visceral melanoma metastases after adrenalectomy supports the role of glucocorticoids in melanoma progression [29].…”
Section: Discussionmentioning
confidence: 83%
“…En los casos con evidencia de afectación de órganos sólidos, el pronóstico es mejor para las metástasis pulmonares (M1b) que para el resto de órganos (M1c). Sin embargo, la resección completa de las lesiones, entendida como la exéresis de las metástasis clínicas y radiológicas con márge-nes libres, puede mejorar la supervivencia de estos pacientes 5 . La presencia de metástasis de melanoma en la glándula suprarenal, es una entidad diagnosticada durante el seguimiento de estos tumores de forma incidental puesto que la presencia de síntomas como dolor o sangrado retroperitoneal es poco frecuente.…”
Section: Discussionunclassified
“…La supervivencia media de todos los pacientes fue de 9,3 meses, siendo de 25,7 meses en los operados con intención curativa. En la serie de Collinson y cols 5 , con 186 pacientes con afectación metastásica de la glándula suprarenal por melanoma cutáneo, sólo 23 fueron intervenidos quirúrgicamente por vía abierta, con intención curativa presentando una supervivencia media de 16 meses (rango de 1-55 meses) frente a 5 meses en los pacientes no intervenidos. La recurrencia adrenal fue la localización inicial en 9 de los pacientes intervenidos, en los 14 pacientes restantes, al igual que en nuestro caso, existió una recidiva previa intervenida quirúrgicamente.…”
Section: Discussionunclassified